Elevated CO2 reduced antimony toxicity in wheat plants by improving photosynthesis, soil microbial content, minerals, and redox status - Khamis, Galal; Reyad, Ahmed Mohamed; Alsherif, Emad A.; Madany, Mahmoud M. Y.; Korany, Shereen Magdy; Asard, Han; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Introduction Antimony (Sb), a common rare heavy metal, is naturally present in soils at low concentrations. However, it is increasingly used in industrial applications, which in turn, leads to an increased release into the environment, exerting a detrimental impact on plant growth. Thus, it is important to study Sb effects on plants under the current and future CO2 (eCO2). Methods To this end, high Sb concentrations (1500 mg/kg soil) effects under ambient (420 ppm) and eCO2 (710 ppm) on wheat growth, physiology (photosynthesis reactions) and biochemistry (minerals contents, redox state), were studied and soil microbial were evaluated. Results and discussion Our results showed that Sb uptake significantly decreased wheat growth by 42%. This reduction could be explained by the inhibition in photosynthesis rate, Rubisco activity, and photosynthetic pigments (Cha and Chb), by 35%, 44%, and 51%, respectively. Sb significantly reduced total bacterial and fungal count and increased phenolic and organic acids levels in the soil to decrease Sb uptake. Moreover, it induced oxidative markers, as indicated by the increased levels of H2O2 and MDA (1.96 and 2.8-fold compared to the control condition, respectively). To reduce this damage, antioxidant capacity (TAC), CAT, POX, and SOD enzymes activity were increased by 1.61, 2.2, 2.87, and 1.86-fold, respectively. In contrast, eCO2 mitigated growth inhibition in Sb-treated wheat. eCO2 and Sb coapplication mitigated the Sb harmful effect on growth by reducing Sb uptake and improving photosynthesis and Rubisco enzyme activity by 0.58, 1.57, and 1.4-fold compared to the corresponding Sb treatments, respectively. To reduce Sb uptake and improve mineral availability for plants, a high accumulation of phenolics level and organic acids in the soil was observed. eCO2 reduces Sb-induced oxidative damage by improving redox status. In conclusion, our study has provided valuable insights into the physiological and biochemical bases underlie the Sb-stress mitigating of eCO2 conditions. Furthermore, this is important step to define strategies to prevent its adverse effects of Sb on plants in the future.